Bacteriophage Isolated from Sewage Eliminates and Prevents the Establishment of Escherichia Coli Biofilm - Karla Veloso Gonçalves Ribeiro; Cleberson Ribeiro; Roberto Sousa Dias; Silvia Almeida Cardoso; Sergio Oliveira de Paula; Jose Cola Zanuncio; Leandro Licursi de Oliveira (Tabriz University of Medical Sciences, 2018)
Purpose: Biofilm growth exerts a negative impact on industry and health, necessitating the development of strategies to control. The objective of this work was study the lytic activity of the phage isolated from the sewage network in the formation and degradation of Escherichia coli biofilms. Methods: E. coli cultures were incubated in 96-well polystyrene microplates under controlled conditions to evaluate the biofilm formation. The E. coli cultures and established biofilms were treated with the suspensions of the vB_EcoM-UFV017 (EcoM017) bacteriophage obtained from sewage for 24 hours. The E. coli bacterial density was measured using absorbance at 600 nm and the biofilms were measured by crystal violet staining. Polystyrene coupons were used as support for Scanning Electron Microscopy and Confocal Microscopy to evaluate biofilm formation. Results: The E. coli strains formed biofilms in polystyrene microplates after 48 hours' incubation. The highest EcoM017 phage titer, in the prevention and degradation experiments, reduced the bacterial growth and the quantity of biofilm formed by E. coli in 90.0% and 87.5%, respectively. The minimum dose capable of reducing the biofilms of this bacterium was 101 PFU/mL after 24 hours. The preformed E. coli biofilm mass was reduced 79% post exposure to the phage in the degradation assay. Microscopic analysis confirmed the results obtained in the plates assays. Conclusion: The EcoM017 phage prevented biofilm formation and degraded the E. coli-established ones. The EcoM017 phage isolated from sewage can reduce bacterial attachment and lyse the E. coli associated biofilm cells, offering biotechnological potential applicability for this phage.